2017
DOI: 10.1038/srep40738
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein import - Functional analysis of the highly diverged Tom22 orthologue of Trypanosoma brucei

Abstract: The β-barrel protein Tom40 and the α-helically anchored membrane protein Tom22 are the only universally conserved subunits of the protein translocase of the mitochondrial outer membrane (TOM). Tom22 has an N-terminal cytosolic and a C-terminal intermembrane space domain. It occurs in two variants: one typified by the yeast protein which has a cytosolic domain containing a cluster of acidic residues, and a shorter variant typified by the plant protein that lacks this domain. Yeast-type Tom22 functions as a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
(74 reference statements)
0
21
0
1
Order By: Relevance
“…Depletion of individual ATOM core subunits has variable effects on the architecture of the high molecular weight ATOM complex (32). It has previously been shown that replacement of fulllength ATOM14, the remote Tom22 ortholog of T. brucei, with a truncated variant that lacks the C-terminal intermembrane space (IMS) exposed domain results in a growth arrest and inhibits mitochondrial protein import (45). However, in contrast to the cell line where the entire ATOM14 is depleted, the assembly of the high molecular weight ATOM complex is not affected in the cells expressing the truncated ATOM14 variant (45).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depletion of individual ATOM core subunits has variable effects on the architecture of the high molecular weight ATOM complex (32). It has previously been shown that replacement of fulllength ATOM14, the remote Tom22 ortholog of T. brucei, with a truncated variant that lacks the C-terminal intermembrane space (IMS) exposed domain results in a growth arrest and inhibits mitochondrial protein import (45). However, in contrast to the cell line where the entire ATOM14 is depleted, the assembly of the high molecular weight ATOM complex is not affected in the cells expressing the truncated ATOM14 variant (45).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that replacement of fulllength ATOM14, the remote Tom22 ortholog of T. brucei, with a truncated variant that lacks the C-terminal intermembrane space (IMS) exposed domain results in a growth arrest and inhibits mitochondrial protein import (45). However, in contrast to the cell line where the entire ATOM14 is depleted, the assembly of the high molecular weight ATOM complex is not affected in the cells expressing the truncated ATOM14 variant (45). We thus asked the question if this protein-import-incompetent ATOM complex is still able to translocate tRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ATOM14 is a remote orthologue of yeast Tom22 that has a much shorter cytosolic domain which, similar to the plant Tom22 orthologue Tom9, lacks the clusters of acidic residues found in the yeast protein . Unlike for Tom22 the short cytosolic domain of ATOM14 is not essential for its function …”
Section: Mitochondrial Protein Import In Trypanosomesmentioning
confidence: 99%